Problems Relating to Archiving Nikah Documents in Germany's Arab Mosques - Jaraba, Mahmoud (Journal of Muslims in Europe, 2022)
In this contribution, I examine how Arab imams in Germany draw up and archive documents pertaining to exclusively religious Islamic marriages (nikah). The absence of a central Islamic authority responsible for registering and safeguarding nikah documents in Germany has led to the emergence of a wide range of practices among Arab imams. These include formal registrations of nikahs on pre-printed forms kept in files, boxes or a storeroom; non-standardised documents issued and handled in various different ways; and orally concluded contracts with no documentary trail whatsoever. In this article, I describe and analyse the different approaches to and practices associated with conducting and recording nikahs among Arab imams. I found that some imams try to formalise the documentary trail with a view to protecting the religious rights of spouses and avoiding internal disputes, whereas others lack experience of institutionalised procedures, thus creating what might be described as archival chaos. I argue that, to reduce the likelihood of unintended consequences, a large number of imams in Germany would benefit from receiving help with professionalising their nikah practices and setting up sound mosque administrations and professionally run archives.
Created from Fastlane, Scopus look-up
Keywords: archives; Germany; imam; marriage registrations; mosques; nikah